Islam, Adat, And Conflict Resolution : Study of Mosehe Ritual in TheTolakiPeople of KonaweKonawe Regency, Southeast Sulawesi - Erens Elvianus Koodoh; Idaman Idaman (JICSA : Journal of Islamic Civilization in Southeast Asian, 2013)
Every ethnic group in Indonesia has a local wisdom in terms of conflict resolution. In the context of Tolaki community, they have Mosehe ritual which can be regarded as an example of local wisdom to resolve their conflicts that often occurs in Tolaki community. Literally, Mosehe is a combination of two words: mo and sehe. Mo is doing something, and sehe which means sacred or healthy. Mosehe is an effort of cleansing themselves from all the works that are wrong. Mosehe as one of a conflict resolution at the outset was influenced by the events in the past by successive in that convinced by the younger generation of Tolaki people until this day as the main cause for the necessarily carried out the mosehe ceremony. These events may be saying as the oath , attitudes and actions by the parents / ancestors of Tolaki , which also affected the lives of people Tolaki to this day. In terms of its implementation, the mosehe rituals divided into two parts are mosehemohewu and moseheowose or mosehewonua. Yet, Mosehe in the Tolaki consists of five kinds: mosehendiolu (the ritual of self purification by using egg as victims), mosehemanu (the ritual of self purification by using a chicken as victims), mosehe were (the ritual of self purification by using a dog as victims), mosehengginiku (the ritual of self purification by using a buffalo white as his victims), and mosehendoono (the ritual of self purification by using a man as his victims). Since Islam arrived in this area, some types of mosehe, such as mosehendoono and Mosehedahu were abandoned. As a form of acculturation between Islam and culture in the mosehe ritual looks a kind of a color of Islam, such as mentioning the Bismillah pronunciation, replacement of words Sangiato Ombu Allah.